The complete mitochondrial genome of Caenorhabditis tropicalis n. sp. (Rhabditida: Rhabditidae). (3rd May 2016) - Yang, Shuang-Shuang; Li, Shan; Wang, Guo-Xiu
Abstract: In order to further study the characteristic of Caenorhabditis, the complete mitochondrial genome (mitogenome) of a modal nematode species Caenorhabditis tropicalis n. sp. (previous species name: C . sp. 11) was determined. The results showed that the mitogenome was 13, 874 bp in length, which contained 12 protein-coding genes (PCGs), 2 ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), an AT-rich region and 2 non-coding regions (NCR). The base composition of the heavy strand was 28.12% A, 47.57% T, 15.53% G, and 8.78% C. Furthermore, it is more significant that this mitogenome has two unique features: One is the AT-rich region which had 4 runs of 12 AT dinucleotides and 4 copies of directly repeated sequence (47 bp) within a pair of inverted repeat sequence (13 bp), and the other is that the NCR (130 bp) between tRNA Arg and tRNA Gln of 4 small stem-loop which was described at the first time. This paper firstly expounded the the complete mitogenome of C. tropicalis n. sp. So it can enrich the molecular resource and facilitate the further research of the population genetics and systematics for Caenorhabditis .